Mesoscopic and Microscopic Magmatic Structures in the Quxu Batholith of the Gangdese Belt, Southern Tibet: Implications for Multiple Hybridization Processes - Ma, Xuxuan; Zhao, Zhongbao; Cao, Wenrong; Huang, He; Xiong, Fahui; Cawood, Tarryn; Li, Haibing (Frontiers in Earth Science, 2021)
The Quxu batholith of the Gangdese magmatic belt, southern Tibet, was mainly emplaced during the Early Eocene. It consists of calc-alkaline granitoids with the occurrence of various types of magmatic microgranular enclaves and dikes. Previous studies have demonstrated that magma mixing played a crucial role in the formation of the Quxu batholith. However, the exact mixing/hybridization processes remain an open question. The magmatic microgranular enclaves are ideal proxies to address the magma mixing processes. In the present study, detailed mesoscopic and microscopic magmatic structures have been investigated, in combination with analyses on mineral textures and chemical compositions. Texturally, most of the enclaves are microporphyritic, with large crystals such as clinopyroxene, hornblende, and plagioclase in a groundmass of hornblende, plagioclase, and biotite. Two types of enclave swarms can be distinguished: polygenic and monogenic swarms. Composite dikes as intermediate stages between the undisturbed mafic dike and dike-like monogenic enclave swarms are found. Our results reveal three distinct stages of magma mixing that occurred in the Quxu batholith: they are at depth, during ascent and emplacement, and after emplacement, respectively. At depth, thorough or partial mixing took place between mantle-derived and crust-derived components to produce hybrid magma. Various enclaves and host granitoids are considered cogenetic because both are hybrid rocks produced by the mixing of the two contrasting components in different proportions. This process is followed by the segregation and differentiation processes of the hybrid magma, leading to the formation of host granitoids and many types of magmatic microgranular enclaves. At this stage, mingling and local mixing happened during ascent and emplacement. In the final stage, mafic magma was injected into early fractures in the crystallizing and cooling pluton to form various dikes such as synplutonic dikes, composite dikes, and undisturbed dikes. In summary, our study demonstrates the coupling between the magmatic texture and composition in an open-system batholith and highlights the potential of using enclaves to understand the magma mixing process. The mafic magma was generated from the primitive mantle, whereas the felsic end-member was produced by partial melting of the preexisting juvenile crust.